Determinants of Tax Avoidance in Energy Sector: Audit Opinion, Audit Fees, Firm Age, and Profitability - Vanny Nur Wahyuningtiyas; Dul Muid (DIPONEGORO UNIVERSITY, 2024)
The phenomenon of tax avoidance in Indonesia is still a major concern, especially in the energy sector which is often involved in international transactions so that it is more vulnerable to tax avoidance. Studies the impact of audit opinion, audit fees, company age, and profitability on tax avoidance in Energy companies traded on the IDX during 2019-2023. A quantitative schema was implemented, with multiple linear regression serving as the analytic tool for 80 pre-existing data units. EViews 12 served as the computational engine for the data's treatment. The results showed that audit opinion has a significant positive effect on tax avoidance, while company age has a significant negative effect. In contrast, audit fees and profitability have no significant effect. Although partially not all variables have a significant effect, the four variables simultaneously have a significant effect on tax avoidance. This indicates that the combination of these variables has a strong ability to explain variations in corporate tax avoidance practices.